(untitled) (Journal of Psychiatrists’ Association of Nepal, 2023)
Opioids are commonly used and abused substance worldwide. Tramadol hydrochloride is a synthetic, centrally acting, opiate-like analgesic. Seizure is a rare side effect of tramadol. Tramadol-related seizures are short, tonic-clonic seizures that, like other drug-related seizures, are self-limiting. This epileptogenic effect of tramadol occurs at both low and high doses. We, herein, report the development of seizures after the use of tramadol with increasing dose. We report a 19-year-old man who had opioid dependence syndrome with regular use resulting into multiple episodes of seizures diagnosed as epilepsy for which Sodium valproate had been started.